Factors associated with the need of parenteral nutrition in critically ill patients after the initiation of enteral nutrition therapy - Lopez-Delgado, Juan Carlos; Servia-Goixart, Lluís; Grau-Carmona, Teodoro; Bordeje-Laguna, Luisa; Portugal-Rodriguez, Esther; Lorencio-Cardenas, Carolina; Vera-Artazcoz, Paula; Macaya-Redin, Laura; Martinez-Carmona, Juan Francisco; Marin Corral, Judith; Flordelís-Lasierra, Jose Luis; Seron-Arbeloa, Carlos; et al. (Frontiers in Nutrition, 2023)
Background & aims: Despite enteral nutrition (EN) is the preferred route of nutrition in patients with critical illness, EN is not always able to provide optimal nutrient provision and parenteral nutrition (PN) is needed. This is strongly associated with gastrointestinal (GI) complications, a feature of gastrointestinal dysfunction and disease severity. The aim of the present study was to investigate factors associated with the need of PN after start of EN, together with the use and complications associated with EN.Methods: Adult patients admitted to 38 Spanish intensive care units (ICUs) between April and July 2018, who needed EN therapy were included in a prospective observational study. The characteristics of EN-treated patients and those who required PN after start EN were analyzed (i.e., clinical, laboratory and scores).Results: Of a total of 443 patients, 43 (9.7%) received PN. One-third (29.3%) of patients presented GI complications, which were more frequent among those needing PN (26% vs. 60%, P=0.001). No differences regarding mean energy and protein delivery were found between patients treated only with EN (n=400) and those needing supplementary or total PN (n=43). Abnormalities in lipid profile, blood proteins, and inflammatory markers, such as C-Reactive Protein, were shown in those patients needing PN. Sequential Organ Failure Assessment (SOFA) on ICU admission (Hazard ratio [HR]:1.161, 95% confidence interval [CI].1.053-1.281, P=0.003) and modified Nutrition Risk in Critically Ill (mNUTRIC) score (HR:1.311, 95% CI:1.098-1.565, P=0.003) were higher among those who needed PN.In the multivariate analysis, higher SOFA score (HR:1.221, 95% CI:1.057-1.410, P=0.007) and higher triglyceride levels on ICU admission (HR:1.004, 95% CI:1.001-1.007, P=0.003) were associated with an increased risk for the need of PN, whereas higher albumin levels on ICU admission (HR:0.424, 95% CI:0.210-0.687, P=0.016) was associated with lower need of PN.Conclusions: A higher SOFA and nutrition-related laboratory parameters on ICU admission may be associated with the need of PN after starting EN therapy. This may be related with a higher occurrence of GI complications, a feature of GI dysfunction.Trial registration: ClinicalTrials.gov: NCT03634943.